(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this work we study the existence of new periodic solutions for the well known class of Duffing differential equation of the form x^′′+ c x^′+ a(t) x +b(t) x^3 = h(t), where c is a real parameter, a(t), b(t) and h(t) are continuous T–periodic functions. Our results are proved using three different results on the averaging theory of first order.